Peranan Dukungan Keluarga Penderita Hipertensi Dalam Penggunaan Aplikasi Kesehatan - Rita Oktaviani; Chriswardani Suryawati; Fery Agusman Motuho Mendrofa (Indonesian Journal of Nursing Research (IJNR), 2019)
Hypertension is often found in primary health care facilities and if not followedup can develop into a more serious disease such as myocardial infarction, stroke,kidney failure and can cause death. Health services for non-communicablediseases such as hypertension depend not only on diagnoses and medicalinterventions but also require environmental support and collaboration betweenhealth workers and patients and their families. The effort to fulfill family healthcare tasks in the current era of modernization is one of them by utilizinginformation and communication technology which is the media to bridgecommunication between health workers and the community. The purpose of thisstudy was to determine the family support of hypertensive patients. The numberof samples in this study was 100 families of hypertensive patients. Samplingusing purposive sampling technique. This research was conducted in theSukoharjo Community Health Center area. Analysis of this study using univariateand frequency distribution. The results showed that the average family supportfor hypertensive patients was emotional support of 14.62, award support 20.03,instrumental support 25.67 and informational support 14.57. Based on the results of the study, it can be concluded that the majority of family support forhypertensive patients is in a fairly good category so it needs to be increased again to carry out family empowerment activities. The results of this study can be used as a reference in determining appropriate interventions in increasing family support for hypertensive patients.